Towards a fair hearing for all employees: A case of probationary employee's in Kenya and the right to be heard prior to dismissal - Gathongo, Johana K (Obiter, 2020)
An employer may require a newly hired employee to serve a reasonable period of probation to establish whether or not his or her performance is of an acceptable standard before permanently engaging the employee. Even so, the current provisions relating to termination of probationary employees under the Employment Act, 2007 (EA) remains a source of concern. Currently, an employer may terminate the employment of a probationary employee at will and without affording such employee an opportunity to be heard. The status quo has received firm approval by the Employment and Labour Relations Court accentuating that employers are immune from claims of unfair termination of a probationary employee. This article argues that for termination to be considered procedurally fair whether during a probation period or not, it should be preceded by an opportunity for an employee to state a case in response to the charges levelled against him or her. This article highlights that all laws in Kenya, including the EA are subject to the Constitution, particularly article 41(1) of the Constitution which guarantees “every person” the right to fair labour practice. Equally, article 27 of the Constitution states that everyone is equal before the law and has a right to equal protection and benefit of the law. Allowing employers’ the freedom to terminate employment without following due process certainly open up the floodgates for abuse of the primary purpose of probation. The mere fact that a contract of employment is labelled as “probationary contract” should not be used as a licence by employers to erode the constitutionally entrenched labour rights. The primary purpose of any good law is to advance the achievement of equity and fairness at the workplace. This can only be achieved by protecting vulnerable and marginalised employees such as probationary employees who participate in unpredictable forms of employment. This article maintains that prominence should be on the existence of an employment relationship and fair labour practice as opposed to the existence of a conditional contract of employment. The existence of an employment relationship should serve as the main “port of entry” through which all employees access the rights and protection guaranteed by labour legislation.